2010
DOI: 10.1098/rsbl.2009.0960
|View full text |Cite
|
Sign up to set email alerts
|

Is it only humans that count from left to right?

Abstract: We report that adult nutcrackers (Nucifraga columbiana) and newborn domestic chicks (Gallus gallus) show a leftward bias when required to locate an object in a series of identical ones on the basis of its ordinal position. Birds were trained to peck at either the fourth or sixth element in a series of 16 identical and aligned positions. These were placed in front of the bird, sagittally with respect to its starting position. When, at test, the series was rotated by 90° lying frontoparallel to the bird's starti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
143
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(157 citation statements)
references
References 9 publications
12
143
2
Order By: Relevance
“…Although it is less commonly discussed in the scientific literature, other research studies have shown quite clearly that processing ordinal information may be considered a core cognitive ability (just like the core quantity system) (e.g., [17,27,37,61,62]). …”
Section: Ordinality and Quantitymentioning
confidence: 99%
“…Although it is less commonly discussed in the scientific literature, other research studies have shown quite clearly that processing ordinal information may be considered a core cognitive ability (just like the core quantity system) (e.g., [17,27,37,61,62]). …”
Section: Ordinality and Quantitymentioning
confidence: 99%
“…Although this inherited preference hypothesis provides no account for the culture-specific directionality of SNARC it is consistent with evidence for spatial-numerical mapping preferences in other species, as would be expected from an evolutionary account (cf. Adachi, 2014;Drucker & Brannon, 2014;Gulledge, 2006;Rugani, Kelly, Szelest, Regolin, & Vallortigara, 2010;Rugani, Vallortigara, Vallini, & Regolin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Modern cognitive science provides methods to test these ideas experimentally. We now know that human newborns, and even inexperienced animals such as newly hatched chicks, are able to discriminate objects on the basis of numerosity a few hours after the start of postnatal experience (8,9). When human newborns are presented with auditory sequences of syllables and visual arrays of objects, they look longer at the arrays that correspond to the auditory sequences in number than at arrays differing in number by a 1:3 ratio (8,10).…”
mentioning
confidence: 99%